2007
DOI: 10.1080/13639080601137734
|View full text |Cite
|
Sign up to set email alerts
|

Expansive learning through high school apprenticeship: opportunities and limits

Abstract: This paper examines a high school apprenticeship program with a focus on the opportunities for 'expansive' learning within three different contexts: schools, the training centre and worksites. The authors assume that while young people differ in the degree to which they engage in learning within different sites, the institutional arrangements and features of different learning environments significantly influence their experiences and the quality of their apprenticeships. The authors' analysis of interviews wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 14 publications
3
14
0
1
Order By: Relevance
“…These results are also supportive of the qualitative evidence of Taylor and Watt-Malcolm (2007). A variety of job-related characteristics are also included in Table 4.…”
Section: Other Background Influencessupporting
confidence: 66%
“…These results are also supportive of the qualitative evidence of Taylor and Watt-Malcolm (2007). A variety of job-related characteristics are also included in Table 4.…”
Section: Other Background Influencessupporting
confidence: 66%
“…A primary concern in the compulsory-versus-voluntary-trade debate is the apparent lack of commitment from employers, especially those associated with voluntary trades, to promote apprenticeship training. If apprentices are indentured in a voluntary trade, there is a marked reduction in apprenticeship completions (Taylor & Watt-Malcolm, 2007). Underlying the compulsory-versus-voluntary classification issue is the move to split trades, and it is gaining momentum.…”
Section: Tensions Stakeholders and Policy Changes And Implicationsmentioning
confidence: 99%
“…Furthermore, the skills and knowledge that apprentices learned during their training became lifelong skills which they could draw upon rather than abstract academic theory which could be easily forgotten (Hamilton, 1990;Halpern, 2009;Lerman, 2008;Taylor & Watt-Malcolm (2007). Taylor and Watt-Malcolm (2007) reported that in a study of apprenticeship programs in Canada, students believed that the support and resources available to them were helpful in their development. Furthermore, the dynamics of the workplace exposed students to everyday work life and helped them to understand issues such as organizational culture, power relations at work and discrimination.…”
Section: Studentsmentioning
confidence: 99%
“…Work based learning encompasses an array of work experiences at the workplace that ranges from job shadowing for a few hours or days, internships and school-based simulated learning to youth apprenticeships that can last for more than a year and are seen as more rigorous (Alfeld et al, 2013;Hamilton & Hamilton, 1997;Stone & Lewis, 2012). Work based learning serves several purposes including engaging and motivating students by linking academic work to practical real world experiences, developing workplace skills and competencies, increasing achievement and high school completion rates, enabling students to explore career options, meeting employer needs in the labor market and transitioning students into adulthood, career or higher education (Bailey, Hughes & Moore, 2004;Darche et al, 2009;Hamilton & Hamilton, 1997;Halpern, 2009;OECD, 2010;Stone & Lewis, 2012;Taylor & Watt-Malcolm, 2007). As students engage in WBL, they develop cognitive skills by learning through engagement with ideas and resources, thereby reinforcing academic instruction.…”
Section: Apprenticeships As Work Based Learningmentioning
confidence: 99%
See 1 more Smart Citation